PERENCANAAN KOMUNIKASI IKLAN POLITIK GUBERNUR TERPILIH PADA PILKADA RIAU 2018 - Abdul Aziz; Fatmawati Fatmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study aims to describe about communication planning of political advertisement (ads) by candidate in local election’s Riau 2018. Basically there is no guarantee that can ensure a candidate's victory is determined by the number of political ads displayed along the way. But political ads can be utilized by canditates to attract public attention through creative ideas. This study uses qualitative methods with descriptive analysis. The result of this study showed that the political ads, used by the elected candidates in local election 2018 in Riau, are part of the political marketing communication process carried out by Syamsuar-Edy Nasution and their team. The communication plan was a systematic and comprehensive political decision starting from research, planning, development, trial planning, implementation and monitoring. The strength factor’s is from candidate's himself. While the weakness factors are from regulations, differences perception between the candidate’s successor team and budget constraints.